Preparation and properties of controllable aluminum foam - Leilei Sun; Yanli Wang; Lucai Wang; Fang Wang; Hong Xu; Wenzhan Huang; Xiaohong You (Materials Research Express, 2021)
As an important method for preparing aluminum foam, space holders have the advantages of simple preparation process, controllable porosity, high operation safety, easy to realize the large-scale production and so on. In this paper, sodium thiosulfate (Na _2 S _2 O _3 ) is selected as the new raw material for spacer to replace the traditional spacer (such as urea and salt), which is prepared by melting, injecting into the mold and solidifying. Three kinds of spherical spacer with different diameters were modified, and aluminum foams with three porosity (65%, 70% and 75%) and three pore sizes (Ø2mm, Ø3mm and Ø4mm) were prepared by compaction, dissolution and sintering. The results of metallographic analysis of aluminum foam sintered sample show that the aluminum powder particles bond closely above 600 °C. The quasi-static compression results show that the interaction between aluminum matrix materials and pore structure affects the mechanical properties of foamed aluminum, and the interaction between porosity and pore size affects the mechanical properties of foamed aluminum.